If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 4 = -80 Reorder the terms: 4 + 7x = -80 Solving 4 + 7x = -80 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 7x = -80 + -4 Combine like terms: 4 + -4 = 0 0 + 7x = -80 + -4 7x = -80 + -4 Combine like terms: -80 + -4 = -84 7x = -84 Divide each side by '7'. x = -12 Simplifying x = -12
| 0x+4y=3 | | 4c+6c= | | 9x^2-139x+930=0 | | 3(6-c)-33=27c-5(3+6c) | | 4(2x-8)-2=4(x-3)+2 | | 2495888=x+0.16x | | y=2x-9/3 | | 3x+11=3-x | | A^2+160000=b^2+40000 | | 3(2u-5)-10u= | | 4(2z-8)-2=4(x-3)+2 | | 2k^2-2=146 | | 2k^2+2=146 | | (x+3)(x^2-6x+1)= | | 5x-9=-90 | | 7(3t+1)-14=t-(t+6) | | -20p^-1/5q^-3 | | cos(3x)=0.6 | | 11x-6=4x^2 | | 11x-6=4u^2 | | 10x+10x+x+x=1760 | | 11(z+1)-4(z-1)=2(z-1)+4(z-1) | | (6x^2)-(5x-6)+(7x^2-7)= | | y=-1x+12 | | 5y-3+y+53=8y+50-5y | | s=pir^2+pirs | | (x+7)(x-1)=20 | | 6(4x-8)-7=6(x-2)+65 | | 2(x+3)=7(x-2)-10 | | 2(x+2)=6(x-2)-12 | | 11x-(4x-8)=71 | | 4x+38=7x+5 |